A Critical Study of the Compilation and Authenticity of the Hindu Religious Scripture “Law Code of Manu” - Dr. Muhammad Zakariya (`, 2025)
The Law Code of Manu, also known as the Manusmriti and Manu Dharma Shatra, is one of the most influential and contested texts in Hindu religious, legal, and social thought. This research article undertakes a critical study of its compilation, historical background, and the claims of its authoritative status within Hindu tradition. The paper examines the textual formation of the Manu Dharma Shastra, analyzing its language, structure, and internal inconsistencies in light of historical and philological evidence. It further investigates the socio-religious context in which the text gained prominence, tracing its role in shaping Hindu jurisprudence, caste regulations, and ethical codes. It further examines the major translations, commentaries, and contributions of Orientalist scholars. This study demonstrates that Manu Dharma Shastra is not merely a religious scripture but a socio-legal constitution that shaped the intellectual and moral framework of Hindu society for generations. Keywords: Manu Dharma Shastra, Manusmriti, Hindu Law, Dharmashastra, Textual Authority, Historical Compilation, Translations and Commentaries, Socio-legal System, Hindu Society